Type de personnalité (A) et type de personnalité (B) et leur relation avec le stress psychologique des managers étude de terrain sur un échantillon d’institutions éducatives - dans la Wilaya de Bouira - aissat, meryam; Aitmedjber, badiaa (Journal of Social Sciences and Humanities, 2021)
This study seeks to find out the personality type (A) and the personality type (B) and their relationship to psychological stress among the managers, with a field study by a sample of educational institutions in the Wilayat of Bouira, and to achieve the objectives of the study we used the descriptive-analytical method, and two measures to collect data, a measure of namely the measure of personality type (A, b) “Ben Zeroual Fatiha 2008”, and the psychological pressure perception scale of “1993 Lavenstein”, which was directed on a sample of (64) managers, and we used the program SPSS to analyze the data, and The study found that there is a correlation between the two variables, and that the predominant pattern among managers, is the personality type( A).